Damage to Concrete Structures - De Schutter, Geert (Taylor & Francis, 2013)
Serious degradation mechanisms can severely reduce the service life of concrete structures: steel reinforcement can corrode, cement matrix can be attacked, and even aggregates can show detrimental processes. Therefore, it is important to understand how damage can occur to concrete structures and to appreciate the timing of the actions leading to damage. Damage to Concrete Structures summarizes the state-of-the-art information on the degradation of concrete structures, and gives a clear and comprehensive overview of what can go wrong. Offering a logical flow, the chapters are ordered according to the chronological timing of the actions leading to concrete damage. The author explains the different actions or mechanisms in a fundamental manner, without too many physical or chemical details, to provide greater clarity and readability. The book describes the different causes of damage to concrete, including inappropriate design, errors during execution, mechanisms occurring during hardening of concrete, and actions or degradation mechanisms during service life (hardened concrete). The degradation mechanisms are illustrated with numerous real-world examples and many drawings and photographs taken of actual structures. Written as a textbook for students as well as a reference for professionals, this easy-to-comprehend book gives readers a deeper understanding of the damage that can occur to concrete during the construction process and service.